Proceedings of the 7th International Driving Symposium on Human Factors in Driver Assessment, Training, and Vehicle Design : Dr 2013
DOI: 10.17077/drivingassessment.1469
|View full text |Cite
|
Sign up to set email alerts
|

The Tactile Detection Response Task: Preliminary Validation for Measuring the Attentional Effects of Cognitive Load

Abstract: Summary: Improved measures of the attentional effects of cognitive load are needed to reduce potential crashes caused by secondary tasks performed while driving. The Tactile Detection Response Task (TDRT) in the proposed ISO Draft Standard WD17488 was tested in laboratory and on-road venues with 16 and 15 subjects, respectively. A sensitivity test used a purely cognitive load increase from an easy (0-back) to hard (1-back) auditory-vocal task. The TDRT response time increased by 90±21 msec in the laboratory, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 16 publications
3
23
0
Order By: Relevance
“…The sensitivity, to both visual-manual and pure cognitive secondary tasks, for all four versions of DRT methods has been evaluated in various studies [ 10 , 22 , 23 , 25 , 26 , 27 , 30 ]. Based on the results of these studies, the ISO DRT standard suggests primarily visual and tactile DRT variants to be suitable and sensitive for assessing distracting factors of audio-vocal systems in vehicles [ 9 ].…”
Section: Detection-response Taskmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensitivity, to both visual-manual and pure cognitive secondary tasks, for all four versions of DRT methods has been evaluated in various studies [ 10 , 22 , 23 , 25 , 26 , 27 , 30 ]. Based on the results of these studies, the ISO DRT standard suggests primarily visual and tactile DRT variants to be suitable and sensitive for assessing distracting factors of audio-vocal systems in vehicles [ 9 ].…”
Section: Detection-response Taskmentioning
confidence: 99%
“…In surrogate driving environments, where drivers, instead of driving, watch a driving video recorded from a driver’s perspective, tapping on the pedal brake was also used as a response method [ 34 , 35 ]. Nevertheless, the most common and now standardised response method is a manual response based on a button press [ 9 , 10 , 20 , 30 ]. The ISO standard recommends that a button is attached to the thumb, index finger ( Figure 7 ) or, if requested, any other finger, on the left hand for left-operated vehicles and vice versa, and it is pressed against the wheel to respond to the presented stimuli [ 9 ].…”
Section: Detection-response Taskmentioning
confidence: 99%
“…Among these DRTs, the Tactile Detection Response Task (TDRT), which uses a vibrating stimulus as a probe, has been recommended as a sensitive surrogate measure for driver distraction with a minimal interference of visual and manual modalities in driving (Engström et al, 2005, Mattes et al, 2008, Engström, 2010, Diels, 2011. Young et al (2013) further demonstrated that the TDRT has the sensitivity to detect the attentional effects of cognitive load and the specificity to differentiate the effects of cognitive load from those of visual load, verified in simulated and open-road driving. The purpose of this study was to examine the eye glance patterns of DRTs for assessment of driver distraction during simulated driving.…”
Section: Objectivesmentioning
confidence: 99%
“…Numerous experimental studies -whether brain imaging, laboratory, simulator, test track, or on-road -find that cell phone conversation or other auditory-vocal tasks increase response times to visual events by about 70-200 ms [e.g., 35,36], 36 or have various other relatively minor effects on driver performance, some beneficial and some detrimental [e.g., 40]. However, the current results show that the epidemiological data from 5 real-world driving studies concur (after adjustment for bias) that there is no increase in crash risk from person-toperson cell phone conversations while driving compared to no conversation, whether using hand-held, portable hands-free, or embedded hands-free devices -a result that contradicts the conclusions of many experimental studies.…”
Section: Reasons For Non-elevation Of Crash Rr By Cellular Conversationmentioning
confidence: 99%